A variable-energy proton linear accelerator system and a method of operating a proton beam - DE MICHELE GIOVANNI (2019)
One of the obstacles to the widespread use of proton therapy is the availability of affordable and compact proton sources and accelerators. The use of linear accelerators (Linacs) allow the construction of such a compact source which may be installed in existing medical facilities. However, instability occurs after accelerating units are turned on or off. A proton linear accelerator system configured to provide RF energy 132 during the off-time of the proton beam operating cycle 190 may be used for increasing or maintaining the temperature of cavities. A method of operating a proton beam is also provided which is suitable for irradiating tissue. These may provide an improved settling time. 广泛使用质子疗法的障碍之一是可负担得起的紧凑质子源和加速器的可用性。直线加速器(Linacs)的使用允许构造可以安装在现有医疗设施中的这种紧凑的源。但是，加速单元打开或关闭后会出现不稳定。被配置成在质子束操作循环(190)的断开时间期间提供RF能量(132)的质子直线加速器系统可用于增加或维持腔的温度。还提供了一种适于照射组织的质子束的操作方法。这些可以提供改善的稳定时间。